2013
DOI: 10.1155/2013/286075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Creatine Monohydrate Supplementation on Various Hematological and Serum Biochemical Parameters of Male Albino Mice following Neonatal Hypoxia‐Ischemia Encephalopathy

Abstract: Background. Present study was designed to report the effect of 2% creatine monohydrate supplementation for 8, 12 and 15 weeks on hematology and serum biochemical profile of male albino mouse following hypoxic ischemic insult on postnatal day 10. Methods. 66 Blood samples (2% creatine monohydrate supplemented (N = 34) and unsupplemented (N = 32)) were analyzed for various hematological (blood glucose, packed cell volume, total WBC count, total RBC count) and serum biochemical parameters (cholesterol, AST, ALT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It also has the potential to suppress the generation of free oxygen radicals in the central nervous system that causes cell damage and inactivation of CK (Yar et al 2015). In addition, in neurode-generative animal models, creatine supplementation has been shown to reduce the oxidative stress, improve the brain functioning and attenuate the neuronal disintegration (Iqbal et al 2015) and also improves the recovery of the cerebral blood flow after the cessation of a hypoxic episode (Bain et al 2013). Hypoxic-ischaemic models of neonatal brain damage in rodents have provided support for the neuroprotective effects of creatine.…”
Section: Therapy Focused On Metabolic Energy Levels With Creatinementioning
confidence: 99%
“…It also has the potential to suppress the generation of free oxygen radicals in the central nervous system that causes cell damage and inactivation of CK (Yar et al 2015). In addition, in neurode-generative animal models, creatine supplementation has been shown to reduce the oxidative stress, improve the brain functioning and attenuate the neuronal disintegration (Iqbal et al 2015) and also improves the recovery of the cerebral blood flow after the cessation of a hypoxic episode (Bain et al 2013). Hypoxic-ischaemic models of neonatal brain damage in rodents have provided support for the neuroprotective effects of creatine.…”
Section: Therapy Focused On Metabolic Energy Levels With Creatinementioning
confidence: 99%
“…A similar regime of creatine supplementation (subcutaneous injection of 3 g/kg at four time points, three before HI and the latest 3 h after the injury) in rat pups that underwent HI at P7 resulted in a reduction of brain injury severity and cell loss in the cortex and hippocampus [ 87 ]. Moreover, several studies have shown that creatine supplementation after an HI event is neuroprotective, reducing neuroinflammation and improving cognitive and motor functions [ 271 , 272 , 273 ]. In the light of the positive results available (for a review, see [ 270 ]), it would be interesting to further investigate whether maternal creatine supplementation may protect the fetal brain from neonatal HI.…”
Section: Other Neuroprotective Natural Compoundsmentioning
confidence: 99%
“…Li et al showed that inflammatory cytokines, such as TNF-α and IL-6, could promote HIE-induced neuronal apoptosis in HIE neonatal rats when reaching the peak injury level for 24-72 h after brain injury. [17] Iqbal et al [18] demonstrated that IL-6 had a neuroprotective effect on cerebral ischemia in HIE.…”
Section: The Characteristics Of Hie In Perinatal Neonatesmentioning
confidence: 99%